Local Wisdom Napai-Based STEM Learning (LW-STEM) Improves Creative Thinking (CT) and Communication Skills in Students - Yolida, Berti; T. Marpaung , Rini Rita; Agus Priadi, Median; Maulina , Dina; Ainiyah Cahyani, Inayatul; Hasniza Ibrahim, Nor (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
The objective of this study is to examine whether the implementation of LW Napai-STEM learning can enhance students' creative thinking (CT) and communication skills. The research method used is a quasi-experimental approach using a non-equivalent control group pretest-posttest design. The N-gain of creative thinking skills tested using the Independent Sample t-Test with a significance level of 5% obtained a Sig. (2 tailed) value of 0.01 <0.05. The average N-gain in the experimental class was 0.56 in the